Apoptotic cells in mouse blastocysts are eliminated by neighbouring blastomeres - Jozef Pisko (Nature Portfolio, 2021)
Abstract Apoptosis is a physiological process that occurs commonly during the development of the preimplantation embryo. The present work examines the ability of apoptotic embryonic cells to express a signal promoting their phagocytosis, and quantifies the ability of neighbouring, normal embryonic cells to perform that task. Microscopic analysis of mouse blastocysts revealed phosphatidylserine externalization to be 10 times less common than incidence of apoptotic cells (as detected by TUNEL). In spite of the low frequency of phosphatidylserine-flipping (in inner cell mass, no annexin V staining was recorded), fluorescence staining of the plasma membrane showed more than 20% of apoptotic cells to have been engulfed by neighbouring blastomeres. The mean frequency of apoptotic cells escaping phagocytosis by their extrusion into blastocyst cavities did not exceed 10%. Immunochemically visualised RAC1 (an enzyme important in actin cytoskeleton rearrangement) was seen in phagosome-like structures containing a nucleus with a condensed morphology. Gene transcript analysis showed that the embryonic cells expressed 12 receptors likely involved in phagocytic process (Scarf1, Msr1, Cd36, Itgav, Itgb3, Cd14, Scarb1, Cd44, Stab1, Adgrb1, Cd300lf, Cd93). In conclusion, embryonic cells possess all the necessary mechanisms for recognising, engulfing and digesting apoptotic cells, ensuring the clearance of most dying blastomeres.